Multivariate Risk Aversion, Utility Independence and Separable Utility Functions - Richard, Scott F. (Management Science, 1975)
This paper concerns utility functions for more than one attribute. A new type of risk aversion found only in muitivariate utility functions is defined. Certain behavioral assumptions, which are necessary and sufficient for one of three forms of separable utility functions including the well-known additive form, are given. It is shown that only one of these separable forms, the “negative multiplicative form,” possesses this new type of risk aversion and in particular that the additive form does not.